Theoretical analysis of intensity distribution in diffraction of light by ultrasound in the case of holographic interferometry - KWIEK, Piotr; ŚLIWIŃSKI, Antoni (Archives of Acoustics, 1979)
The theoretical background for optical holographic interferometry used in ultrasonic field investigations is presented. The double-exposure pulse technique, the time averaged technique, and also the stroboscopic real time technique are considered. Formulae for distributions of the light intensity in ultrasonic field holograms are derived for the techniques considered.